Corrosion Behavior of Bitter Almond Oil During Processing. Issue 11 (16th September 2019) - Mao, Xiaohui; Zhu, Hailan; Zhao, Zhong; Yu, Xiuzhu
Abstract: This study aims to explore the corrosion behavior of bitter almond oil (BAO) during processing. Hydrocyanic acid (HCN) and benzoic acid in oil are speculated as the main components that corrode the screw oil expeller. Immersion and simulation corrosion tests are carried out to verify this hypothesis. Immersion test results show that crude BAO (CBAO) containing 5.07 ± 0.06 mg kg −1 benzoic acid and 4.25 ± 0.04 mg kg −1 HCN exhibits corrosive effects on steel. Simulation corrosion test results indicate that the addition of CN − or benzoic acid has significant effect on the corrosion of steel. Specifically, at ≥1 × 10 4  mg kg −1 benzoic acid concentration or ≥5 mg kg −1 CN − concentration, the mass of steel blocks in oil decreases and the contents of Fe, Zn, Al, and Mg ions in oil increase significantly. Therefore, HCN in CBAO is the main cause of screw oil expeller corrosion in BAO processing and benzoic acid is the secondary cause. Practical Applications : The corrosion behavior of CBAO not only damages the integrity of the screw oil expeller but also increases the dissolution of toxic metals from the components into oil. The study of corrosion has practical value in taking effective measures, such as detoxification before pressing and addition of natural inhibitors, to reduce corrosion and ensure the quality of CBAO. Corrosion study provides the basis for the selection of steel materials of screw oil expeller. Abstract : The corrosion behavior of bitter almond oil (BAO) that occurs in oil press during BAO production is studied. Crude bitter almond oil (CBAO), refined bitter almond oil (RBAO), and rapeseed oil are selected to determine the cause of corrosion and immersion tests and simulation corrosion tests are carried out. Hydrocyanic acid in CBAO is the main cause of screw oil expeller corrosion in BAO processing, and benzoic acid is a secondary cause.